ADOLESCENTS’ KNOWLEDGE ABOUT STRESS AND DEPRESSION QUESTIONNAIRE (AKSDQ): VALIDITY AND RELIABILITY TEST - Putra, Kusuma Wijaya Ridi; Prawito; Zatihulwani, Eliza Zihni; Rustanti, Elly (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Adolescence is a period of growth that is very vulnerable to stress. This is due to the relatively high demands on adolescents, both in the field of education and daily life. Objective: The purpose of this study was to analyze the results of the validity and reliability tests of the Adolescents' Knowledge about Stress and Depression Questionnaire (AKSDQ). Methods: This study used a descriptive analysis research design with a cross-sectional approach. The research was carried out in August 2023 at Senior High School Darul Ulum 3 Peterongan Jombang. The instrument used in this study was the Adolescents' Knowledge about Stress and Depression Questionnaire (AKSDQ). This questionnaire consists of 10 items with 7 items in the form of positive statements and 3 items in the form of negative statements. This questionnaire uses the true and false statement method. Data analysis was carried out in this study using SPSS 21. The data analysis presented is the mean, standard deviation, Item-Content Validity Index (I-CVI), and Kuder-Richardson. Result: Based on the research results, it was found that the Adolescents' Knowledge about Stress and Depression Questionnaire (AKSDQ) had a good enough reliability value marked by a KR-20 value of .601. In addition, the results of the validity test using the Item-Content Validity Index (I-CVI) method showed that the Mean I-CVI is 0.90. Conclusion: The results of this study indicated that the Adolescents' Knowledge about Stress and Depression Questionnaire (AKSDQ) can be used in a study to assess the level of knowledge of adolescents related to stress and depression.